From catharsis to the cathartic: toward a post-dramatic theory of representation (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The understanding of the notion of catharsis has been through constant theoretical debates and controversies throughout history of theater. Different perspectives were born entangled to varied social, cultural, and political contexts. The notion of catharsis related to classical tragedy, as defined by Aristotle, has since been explored by theater movements until its apparent refusal in contemporary theater, especially in the so-called post dramatic theater. This article does not aim to explore yet a new understanding of catharsis in the contemporary. Instead, it examines how experiments in post dramatic theater distance themselves from the Aristotelian notion and establish a new perspective focused on the cathartic effect, an analysis that traverses the Lacanian psychoanalysis.
Keywords: catharsis; cathartic; voice; gaze; desire